Population dynamics, fire, and reproductive ecology of Oldenburgia grandis (Asteraceae), an unusual fynbos tree endemic to the Eastern Cape - Mostert, Emma Charlotte (Rhodes University, Faculty of Science, Botany Department)
Thesis embargoed. Possible release date set for early 2024.
Keywords: Uncatalogued